Analisis Butir Soal Penilaian Akhir Tahun Kelas VI Mata Pelajaran Matematika Madrasah Ibtidaiyah Ar-Roudhoh 2023 - Budi, Tegar Setia (Mentari : Journal of Islamic Primary School, 2023)
Education is the main key to the nation's progress, and efforts to strengthen the quality of education must continue to be guaranteed so that Indonesia is competitive in this era of globalization. The role of educators and the learning process is an important part of determining the quality of education. Based on the results of interviews with researchers, 16 teachers of MI AR ROUDHOH Jember showed that 30% of the teachers in the school out of a total of 30 teachers in the school had not done item analysis and the rest had done item analysis. questions but have not been developed to determine the difficulty level of the questions. Based on the results of these interviews, the researcher felt the need to find out the quality of the items and the abilities of elementary school students, especially MI AR ROUDHOH Jember. The research conducted was in the form of evaluation research. This study used a quantitative descriptive method to analyze the index of difficulty level, validity and reliability of the items being tested as well as the ability level of class VI students, that out of 25 questions there were 5 questions in the category of easy, very easy and moderate in the sense that students were able to answer questions (question number 1,2,7,13,24), 5 questions in the difficult category (questions number 5,6 8,9,11) and 15 questions in the very difficult category